2021
DOI: 10.1186/s12889-021-11230-9
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic inequalities in 29 childhood diseases: evidence from a 1,500,000 children population retrospective study

Abstract: Background Socioeconomic position (SEP) powerfully affects health status in the childhood population. However, the knowledge of which diseases are more affected by SEP and whose outcomes could be improved by having a more equitable society remains uncertain on a population basis. Methods We measured socioeconomic and gender inequalities in the pre-COVID-19 era for 29 diseases in the entire childhood population in Catalonia to identify which disease… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 45 publications
0
18
0
1
Order By: Relevance
“…Children living in disadvantaged or marginalized circumstances have worse physical and mental health than their more advantaged peers [1 ▪▪ ,2–4]. This relationship holds true for conditions ranging from obesity to anxiety, infectious diseases to low birthweight [5]. There is an established social gradient in health from the bottom to the top of the socio-economic spectrum making this a societal issue [6].…”
Section: Introductionmentioning
confidence: 99%
“…Children living in disadvantaged or marginalized circumstances have worse physical and mental health than their more advantaged peers [1 ▪▪ ,2–4]. This relationship holds true for conditions ranging from obesity to anxiety, infectious diseases to low birthweight [5]. There is an established social gradient in health from the bottom to the top of the socio-economic spectrum making this a societal issue [6].…”
Section: Introductionmentioning
confidence: 99%
“…Definitions have been proposed to group children with medically complex or chronic conditions [ 29 – 31 ], with a prevalence estimated to be between 13 and 18% and who also show healthcare inequities [ 31 , 32 ]. Several studies have provided data on specific chronic diseases or not are more affected by socioeconomic positions based on and other diseases [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the socioeconomic status of an individual, which affects their burden of spending on such care services, was identified as a specific factor contributing to the poor utilization of healthcare services. Numerous studies have reported that SES is associated with healthcare utilization according to parental education and household income [9,12,17,18,24,27]. Another study reported that the burden of medical expenses for preschool children is lower than in other nations due to universal medical insurance and regional government subsidies for children's medical expenses [28].…”
Section: Discussionmentioning
confidence: 99%
“…Reportedly, hospital utilization is higher in urban than rural areas, and hospitals in rural areas typically have less resources than the facilities in urban areas. Furthermore, since the health disparities related to the association between gender and age have already been studied in children [11][12][13][14][15][16][17][18], there is a need for research on the health disparities related to the association between SES and healthcare utilization. This study assumed that healthcare utilization might vary depending on SES categories.…”
Section: Introductionmentioning
confidence: 99%